PENGARUH KUALITAS PELAYANAN, FASILITAS DAN KEPERCAYAAN TERHADAP KEPUASAN KELUARGA PASIEN PADA RS. DHARMAHUSADA PROBOLINGGO - Agustina Pujiastutik (Yudishtira Journal : Indonesian Journal of Finance and Strategy Inside, 2021)
Satisfaction or dissatisfaction is a person's feeling of pleasure or disappointment that comes from a comparison between his impression of real/actual product performance and expected product performance. The purpose of this study is 1) To find out the influence of service quality, facilities and trust variables simultaneously on patient family satisfaction in hospitals. Dharma Husada Probolinggo 2) To determine the effect of variables in Quality of Service, Facilities and Trust partially on Patient Family Satisfaction in hospitals. Dharma Husada Probolinggo. 3) To find out the variables that have a dominant effect between the variables of Service Quality, Facilities and Trust in Patient Family Satisfaction in hospitals. Dharma Husada Probolinggo. Researchers used descriptive with a causal associative approach and sampled as many as 40 respondents, data collection methods using questionnaires and sampling techniques using random sampling. The analysis tools used are questionnaire tests consisting of validity tests and reliability tests, classical assumption tests, multiple regression tests, determination tests, test hypotheses consisting of t tests, F tests and dominant tests. The results of the validity test study showed all valid question items were above 0.320 and reliability test results showed reliable results above 0.60. The Normality test shows normal distributed data. The Multicollinierity test shows that the free variable (X) and the bound variable (Y) have no correlation between independent variables or a free regression model of multicollinearity. Heteroskedasticity tests showed no heteroskedasticity. The autocorrelation test shows no autocorrelation occurs. The F test showed that free variables had a simultaneous effect on satisfaction (Y) with Fhitung values > Ftabel (361,659 > 3,259) (sig. 0,000 < 0.05). The t test showed that the service quality variable (X1) had a partial effect on satisfaction (Y) with a value of > ttabel (14,765 ? 2,024) (sig. 0,000 ?.025). And the facility variable (X2) partially affects satisfaction (Y) with a value of ? ttabel (6,199 ? 2,024) (sig. 0,000 ? 0.025). The trust variable has a partial effect on satisfaction (Y) with a value of ? ttabel (3,342 ? 2,024) (sig.0,000 ? 0.025). This study supports the results of research conducted by Susanti (2017), Wulandari (2017) and Umayyad (2017).